AutoMATiC: Code Generation of Model Predictive Control Algorithms for Microcontrollers - Chaber, Patryk; Lawrynczuk, Maciej (IEEE transactions on industrial informatics, 2020)
This article describes the AutoMATiC software system that generates the C code of software implementation of model predictive control algorithms for a chosen target microcontroller. The following components of the AutoMATiC tool are described: the system structure, workflow, and software framework. The system includes a transcompiler, a simulator, and a profiler. To discuss effectiveness of the system, a dynamic process with two inputs and two outputs is considered. The following advantages of the AutoMATiC system are emphasized: simplicity of use, the possibility of activating/deactivating online different control algorithms in a seamless way, the possibility of adding new control algorithms in a straightforward way, and code efficiency.